Charge-lattice coupling and the dynamic structure of the U–O distribution in UO2+x - Lewis, Jarrod; Springell, Ross; Bell, Christopher; Nicholls, Rebecca; Wasik, Jacek; Harding, Lottie; Gupta, Mahima; Pakarinen, Janne; Baldinozzi, Gianguido; Andersson, David; Guo, Xiaofeng; Conradson, Steven D. (Frontiers in Nuclear Engineering, 2024)
The different structures and behaviors of UO2+x observed in crystallographic and local structure measurements were examined by extended X-ray absorption fine structure (EXAFS) measurements of pristine UO2.0, p+ and He2+ irradiated UO2.0, and, at multiple temperatures, bulk U4O9 and U3O7 and thin film U4O9-δ on an epitaxial substrate. The disorder caused by irradiation is mostly limited to increased widths of the existing U–O/U pair distributions, with any new neighbor shells being minor. As has been previously reported, the disorder caused by oxidative addition to U4O9 and U3O7 is much more extensive, resulting in multisite U–O distributions and greater reduction of the U–U amplitude with different distributions in bulk and thin-film U4O9. This includes the significant spectral feature near R = 1.2 Å for all U4O9 and U3O7 samples fit with a U-oxo type moiety with a U–O distance around 1.7 Å. In addition to indicating that these anomalies only occur in mixed valence materials, this work confirms the continuous rearrangement of the U–O distributions from 10 to 250 K. Although these variations of the structure are not observed in crystallography, their prominence in the EXAFS indicates that the dynamic structure underlying these effects is an essential factor of these materials.